The prevalence of anemia among the tribal children from the western districts of West Bengal, India - Dolai, Tuphan Kanti; Mondal, Somnath; Jain, Manisha; Mandal, Prakas Kumar (International Journal Of Community Medicine And Public Health, 2021)
Background: Tribal population in West Bengal constitutes a significant proportion (5.1%) and the vulnerable group because of lower socio-economic status, poor literacy rate and malnutrition. The present study was conducted to evaluate hemoglobin level and prevalence of anemia among the tribal children from the western districts of West Bengal, India. Methods: A cross-sectional study was conducted on school going (class I to class VIII) tribal children (≥5 to <13years) during March 2019 to February 2020. A complete blood count was done by automated blood cell counter and anemia was classified as per WHO criteria. They were also tested for markers of common nutritional anemias (serum ferritin, serum vitamin B12 and serum folate). Data entry and analysis was done on SPSS version 15. A p-value of <0.05 was considered statistically significant. Results: Total 1, 010 tribal children were included with male:female=1:1.35. Among these, 46.34% (n=468) children had anemia. Among all anemic children 47.65% (n=223), 51.93% (n=243/468) and 0.42% (n=2) respectively had mild, moderate and severe anemia. There was a high prevalence (81.68%) of microcytic red blood cells in the total cohort; among anemic children, 53.94% have microcytosis while no macrocytosis was revealed. Among all grade anemias, iron, folate and vitamin B12 deficiency were found in 44.65% (n=209/468), 13.24% (n=62/468) and 25% (n=117/468) respectively. Conclusions: The prevalence of anemia among tribal children of West Bengal is a matter of concern. The high prevalence of microcytic indices in non-anemic population highlights the dire need for screening for the causes of anemia in this population.